Pengelolaan Pembelajaran Matematika Berbasis Al Qurâan di Sekolah Menengah Pertama - Saksono, Deky Yudha; Sutama, Sutama (Jurnal Varidika: Varia Pendidikan, 2015)
This study aims to describe the mathematicsbased learning management Qurâan conducted in Junior High School Kendal district, Central Java. This study uses the approach of research and development. Data collection techniques, observation, interviews, and documentation. Validity of data with triangulation techniques and triangulation of sources. Results of the study: (1) The management of learning that has been done is still using school math learning in general, (2) Management based math learning the Qurâan through the stages of the addition of paragraph choices on the subject matter has not been made, (3) based learning management Qur âan has not been effective so no link between mathematics and the Qurâan.